2005
DOI: 10.1177/1356766705050842
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of wine festival attendees’ motivations: A synergy of wine, travel and special events?

Abstract: As special-interest tourism, wine tourism is becoming increasingly important for wine-growing regions. But wine marketers are faced with a paucity of empirical data when examining wine tourists’ characteristics and behaviour. This issue needs to be addressed if marketers want to implement more effective strategies to target the market. Visiting wine festivals is an important component in the complete construct of wine tourism. What might have motivated the participants to visit such an event has become critica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
188
0
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 250 publications
(204 citation statements)
references
References 21 publications
(23 reference statements)
9
188
0
7
Order By: Relevance
“…By attracting people interested in wine, wine festivals have become a key element of both the wine and tourism industries (J. J. Yuan, Cai, Morrison, & Linton, 2005a, 2005b. As wine regions have been at the forefront of developing festivals as part of a total wine (tourism) experience, the majority of wine festival studies tend to take place within large wine producing regions and wine tourism destinations.…”
Section: Wine Tourism and Wine Festivalsmentioning
confidence: 99%
See 2 more Smart Citations
“…By attracting people interested in wine, wine festivals have become a key element of both the wine and tourism industries (J. J. Yuan, Cai, Morrison, & Linton, 2005a, 2005b. As wine regions have been at the forefront of developing festivals as part of a total wine (tourism) experience, the majority of wine festival studies tend to take place within large wine producing regions and wine tourism destinations.…”
Section: Wine Tourism and Wine Festivalsmentioning
confidence: 99%
“…In addition, such studies naturally link festivals with wine tourism development (J. J. Yuan et al, 2005a;J. J. Yuan, Morrison, Cai, & Linton, 2008).…”
Section: Wine Tourism and Wine Festivalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this model has been used as an instrument in various studies across industries, the SERVQUAL has received many criticisms from some scholars (e.g., Cronin & Taylor, 1992;Brown et al, 1993) and they are opposed to the use of SERVQUAL to measure service quality due to the differences in industry characteristics. However, other scholars have confirmed that the SERVQUAL instrument is applicable in the tourism industry (e.g., Fick & Ritchie, 1991;Yuan et al, 2005).…”
Section: Service Qualitymentioning
confidence: 99%
“…Njih možemo okarakterisati kao posetioce vinograda, vinarija vinskih festivala i vinskih prodavnica sa ciljem odmora [2]. Vinski turisti su obrazovani, imaju veća primanja i visoko interesovanje za vino [11].…”
Section: Komparacija Internet Stranaunclassified